Preparation of Nitrogen-Doped Carbon Material from Monosodium Glutamate and Its Catalytic Performance - Ying Mei Zhou; Xiao Hui Wang; Ke Ying Cai; Ji Ming Wu; Peng Wang; Ming Song (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
N-doped carbon materials (NCMs) are generally used as electrode materials, and seldom used as catalysts in chemical reaction. In this work, NCMs were prepared by high-temperature pyrolysis using monosodium glutamate as sources of both carbon and nitrogen, magnesium acetate as a porogen, and nickel hydroxide as a graphitization catalyst. The catalytic performance of NCMs was investigated in the reduction of 4-nitrophenol (4-NP) with potassium borohydride at 30 ºC. As metal-free catalysts, all of the NCMs can catalyze the reaction. The graphitization degree and N-doped amount of NCM have a great influence on the catalytic activity. The NCM annealed at 800 ºC has higher activity and stability. The reaction rate constant can reach 0.57 min-1, and the activation energy was about 36.4 kJ/mol.